Addiction treatment trials: how gender, race/ethnicity, and age relate to ongoing participation and retention in clinical trials - Korte JE; Rosa CL; Wakim PG; Perl HI (Dove Medical Press, 2011)
Jeffrey E Korte1, Carmen L Rosa2, Paul G Wakim2, Harold I Perl21Division of Biostatistics and Epidemiology, Medical University of South Carolina, Charleston, SC, 2Center for the Clinical Trials Network, National Institute on Drug Abuse, Bethesda, MD, USAIntroduction: Historically, racial and ethnic minority populations have been underrepresented in clinical research, and the recruitment and retention of women and ethnic minorities in clinical trials has been a significant challenge for investigators. The National Drug Abuse Treatment Clinical Trials Network (CTN) conducts clinical trials in real-life settings and regularly monitors a number of variables critical to clinical trial implementation, including the retention and demographics of participants.Purpose: The examination of gender, race/ethnicity, and age group differences with respect to retention characteristics in CTN trials.Methods: Reports for 24 completed trials that recruited over 11,000 participants were reviewed, and associations of gender, race/ethnicity, and age group characteristics were examined along with the rate of treatment exposure, the proportion of follow-up assessments obtained, and the availability of primary outcome measure(s).Results: Analysis of the CTN data did not indicate statistical differences in retention across gender or race/ethnicity groups; however, retention rates increased for older participants.Conclusion: These results are based on a large sample of patients with substance use disorders recruited from a treatment-seeking population. The findings demonstrate that younger participants are less likely than older adults to be retained in clinical trials.Keywords: addiction treatment, age, ethnic minorities, gender difference, substance use disorders, race, recruitment, retention, clinical trials